Real‐world impact following initiation of interferon‐free hepatitis C regimens on liver‐related outcomes and all‐cause mortality among patients with compensated cirrhosis. Issue 3 (26th November 2019) - McDonald, Scott A.; Pollock, Kevin G.; Barclay, Stephen T.; Goldberg, David J.; Bathgate, Andrew; Bramley, Peter; Dillon, John F.; Fraser, Andrew; Innes, Hamish A.; Kennedy, Nicholas; Morris, Judith; Went, April; et al.
Abstract: Few studies have investigated clinical outcomes among patients with cirrhosis who were treated with interferon (IFN)‐free direct‐acting antiviral (DAA). We aimed to quantify treatment impact on first decompensated cirrhosis hospital admission, first hepatocellular carcinoma (HCC) admission, liver‐related mortality and all‐cause mortality among a national cohort of cirrhotic patients. Through record linkage between Scotland's HCV Clinical Database and inpatient/day‐case hospitalization and deaths records, a study population comprising chronic HCV‐infected patients with compensated cirrhosis and initiated on IFN‐free DAA between 1 March 2013 and 31 March 2018 was analysed. Cox regression evaluated the association of each clinical outcome with time‐dependent treatment status (on treatment, responder, nonresponder or noncompliant), adjusting for patient factors including Child‐Pugh class. Among the study population (n = 1073) involving 1809 years of follow‐up, 75 (7.0%) died (39 from liver‐related causes), 47 progressed to decompensated cirrhosis, and 28 developed HCC. Compared with nonresponders, treatment response (96% among those attending their 12 weeks post‐treatment SVR test) was associated with a reduced relative risk of decompensated cirrhosis (hazard ratio [HR] = 0.14; 95% CI: 0.05‐0.39), HCC (HR = 0.17; 95% CI: 0.04‐0.79), liver‐related death (HR = 0.13; 95% CI: 0.05‐0.34) and all‐cause mortality (HR = 0.30; 95% CI: 0.12‐0.76). Compared with responders, noncompliant patients had an increased risk of liver‐related (HR = 6.73; 95% CI: 2.99‐15.1) and all‐cause (HR = 5.45; 95% CI: 3.07‐9.68) mortality. For HCV patients with cirrhosis, a treatment response was associated with a lower risk of severe liver complications and improved survival. Our findings suggest additional effort is warranted to address the higher mortality among the minority of cirrhotic patients who do not comply with DAA treatment or associated RNA testing.